Research on the Development and Innovative Management Models of Cultural Creative Parks - Li, Ting (Transactions on Social Science, Education and Humanities Research, 2024)
Under the backdrop of the knowledge economy and globalization, the cultural creative industry, with its unique innovativeness and high added value, has gradually become a new driving force for economic development. Cultural creative parks, as vital platforms for the development of the cultural industry, have aggregated numerous creative enterprises and talents, becoming significant platforms for urban cultural innovation and cultural exchange. The innovation in development and management models of these parks is crucial for enhancing the competitiveness of the cultural industry and promoting urban cultural prosperity. However, with the rapid development of the cultural creative industry, traditional management models can no longer meet the developmental needs of these parks. Therefore, it is imperative to first clarify the functions of cultural creative parks, analyze the factors influencing their development one by one, base strategies on actual conditions, actively explore development and management models, establish market positioning, build on traditional management philosophies with modern management concepts, and strengthen brand building through resource optimization and integration. Implementing these strategies can effectively enhance the operational efficiency and service quality of cultural creative parks, attract more high-quality enterprises and talents, and promote the sustained and healthy development of the parks.